The Improvement of Secondary Student’s Creative Thinking by STEM Projects Case Study: Suwanpaiboon School - Saelo, Bunyisa; Cheama, Suffian (Journal of Information and Learning [JIL], 2020)
The aims of this research were 1) to compare students’ creative thinking before and after using STEM projects, and 2) to investigate students’ beliefs in using STEM projects for developing their creative thinking. Subjects were 30 Suwanpaiboon School students who were selected through purposive sampling. The target group was three students selected from the sample. The tools for collecting data were article creative thinking test and article questionnaire. The research has a quasi-experimental design. Quantitative (using t-test analysis) and qualitative data analyses (describing) were used in this study. The results illustrated that 1) the students had a higher level of creative thinking at a confidence level of .01 after being involved in the STEM projects, and 2) all the target students believed that their creative thinking could be improved by STEM projects.